The role of naturally acquired intracellular Pseudomonas aeruginosa in the development of Acanthamoeba keratitis in an animal model. - Binod Rayamajhee; Mark Willcox; Fiona L Henriquez; Ajay Kumar Vijay; Constantinos Petsoglou; Gauri Shankar Shrestha; Hari Kumar Peguda; Nicole Carnt (Public Library of Science (PLoS), 2024)
Background Acanthamoeba is an environmental host for various microorganisms. Acanthamoeba is also becoming an increasingly important pathogen as a cause of keratitis. In Acanthamoeba keratitis (AK), coinfections involving pathogenic bacteria have been reported, potentially attributed to the carriage of microbes by Acanthamoeba. This study assessed the presence of intracellular bacteria in Acanthamoeba species recovered from domestic tap water and corneas of two different AK patients and examined the impact of naturally occurring intracellular bacteria within Acanthamoeba on the severity of corneal infections in rats. Methodology/principal findings Household water and corneal swabs were collected from AK patients. Acanthamoeba strains and genotypes were confirmed by sequencing. Acanthamoeba isolates were assessed for the presence of intracellular bacteria using sequencing, fluorescence in situ hybridization (FISH), and electron microscopy. The viability of the bacteria in Acanthamoeba was assessed by labelling with alkyne-functionalized D-alanine (alkDala). Primary human macrophages were used to compare the intracellular survival and replication of the endosymbiotic Pseudomonas aeruginosa and a wild type strain. Eyes of rats were challenged intrastromally with Acanthamoeba containing or devoid of P. aeruginosa and evaluated for the clinical response. Domestic water and corneal swabs were positive for Acanthamoeba. Both strains belonged to genotype T4F. One of the Acanthamoeba isolates harboured P. aeruginosa which was seen throughout the Acanthamoeba's cytoplasm. It was metabolically active and could be seen undergoing binary fission. This motile strain was able to replicate in macrophage to a greater degree than strain PAO1 (p<0.05). Inoculation of Acanthamoeba containing the intracellular P. aeruginosa in rats eyes resulted in a severe keratitis with increased neutrophil response. Acanthamoeba alone induced milder keratitis. Conclusions/significance Our findings indicate the presence of live intracellular bacteria in Acanthamoeba can increase the severity of acute keratitis in vivo. As P. aeruginosa is a common cause of keratitis, this may indicate the potential for these intracellular bacteria in Acanthamoeba to lead to severe polymicrobial keratitis.